ANALYSIS OF THE TEACHER'S EFFORTS IN IMPROVING STUDENTS' SPEAKING SKILL AT SMP NEGERI 4 MANOKWARI - Sulistyahadi Sulistyahadi; Hawa Hasan; Albarthina Izak (LP4MK STKIP PGRI Lubuklinggau, 2023)
The objective of this research was to describe teachers' efforts in improving students' speaking skills at SMPN 4 Manokwari. The method used was descriptive qualitative research. The subject of this research was the English teacher at SMP Negeri 4 Manokwari. There are two teacher’s that have become the subject of this research. The data of this research were collected by observation, interview, and documentation. Data analysis in this research with three steps namely, data reduction, display data and conclusing drawing. The result of this research indicate that the efforts made by the teacher in improving students’ English speaking skills include using strategies or techniques for singing, telling stories, games, and practicing conversations. These efforts have a big impact on improving English speaking skills.